2002
DOI: 10.1046/j.1365-2664.2002.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of reducing population density on contact rates between brushtail possums: implications for transmission of bovine tuberculosis

Abstract: Summary 1.Interactions during mating are thought to be an important mechanism for transmission of tuberculosis (Tb) Mycobacterium bovis in the brushtail possum Trichosurus vulpecula . However, little information is available on the frequency of contacts between males and females in oestrus during the breeding season, and the relationship between mating contacts and population density. 2. We used radio-telemetry to record contacts between male and oestrous and nonoestrous female possums, and determined paternit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 39 publications
0
81
1
Order By: Relevance
“…In addition, fertility control can induce behavioural changes, such as reproductionrelated long-distance movements, that reduce disease transmission rates (e.g. Caley and Ramsey 2001;Ramsey et al 2002;Ramsey 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fertility control can induce behavioural changes, such as reproductionrelated long-distance movements, that reduce disease transmission rates (e.g. Caley and Ramsey 2001;Ramsey et al 2002;Ramsey 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The limited field studies available have not confirmed a linear density-dependent relationship of disease transmission (Caley et al, 1998;Begon et al, 1999;Ramsey et al, 2002;Ji et al, 2005;Woodroffe et al, 2006). The assumption of linear density dependence affecting fox rabies transmission is questionable; threshold densities to decrease trans- In the case of certain bat species, the TM population is also the reservoir.)…”
Section: 2mentioning
confidence: 99%
“…Indirect co-benefits include reductions in trace gas emissions arising from reductions in stock numbers and fertiliser application, reduced expenditure on farm maintenance, and reductions in both on-and offfarm energy use. However, additional costs are also presently excluded from this initial economic analysis, with possible significant expenditure on fencing, and on control of weeds or animal pests (e.g., possums, that spread bovine tuberculosis; [37]) that may establish in wooded land. Further, although the C accumulation rates used in the present economic assessment are long-term means, even lower accumulation rates may occur initially on a unit area basis until canopy closure over the entire area occurs.…”
Section: Estimating the Economic Value Of "Carbon Farming"mentioning
confidence: 99%